Impact of particle size of pulverized citrus peel tissue on changes in antioxidant properties of digested fluids during simulated in vitro digestion - Yidi Cai; Wei Qin; Sunantha Ketnawa; Yukiharu Ogawa (Food Science and Human Wellness)
To examine the effect of mechanical processing for plant-based materials on antioxidant properties during digestion, relationships between the size of pulverized plant tissue and changes in antioxidant activities during simulated in vitro digestion were investigated. The citrus peel tissue was pulverized and classified into four powder fractions followed their particle size distributions as 125 − 180 μm, 180 − 355 μm, 355 − 500 μm and 500 − 710 μm. These fractions were regarded as a plant tissue model with various degrees of cell damages. Powder samples were collected during the digestion and measured their particle sizes and colors. Besides, total phenolic content and antioxidant activities of digested fluid were also evaluated. The results showed that the powder color of smaller particles were significantly changed than the bigger ones. The bio-properties of digested fluid for the bigger particle sizes comparatively retained more than smaller ones at the simulated gastric stage. It also showed mostly stable during simulated gastric or small intestinal digestion stage. This suggested that the release of bioactive compounds from plant tissues during digestion could be related to their structural attributes such as degrees of cell damages which could be affected by processing methods and conditions. Keywords: Plant-based food, Tissue structure, Antioxidant activity, Simulated in vitro digestion, Cell matrix